STRATEGI PENGELOLAAN BISNIS KULINER WARALABA DI TINJAU DARI KUALITAS PRODUK DAN MUTU PELAYANAN - Dwi Yoso Nugroho; Joko Triyono (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
This study aims to determine the influence of product quality, and service quality on the purchasing decisions of Baba Rafi Kebab consumers. This study used a questionnaire as data collection material, which was analyzed for multiple linear regression using SPSS 25 software. Independent variables consist of product quality, and service quality of purchasing decisions as dependent variables. The results of this study show that product quality, and service quality both jointly and individually have an influence on purchasing decisions positively and significantly.Keywords: Product Quality, Service Quality, Purchasing Decisions, and Business Management